175k views
5 votes
2-(3-a)=-4 please help me i did not understand the question

User Drakosha
by
6.8k points

1 Answer

2 votes

Answer:

A= -3

Explanation:

The parenthesis means multiplication with the number before it, it is a negative blank meaning you just switch the signs. 3-a becomes a-3. then you add 2 into it, making the equation A-1=-4. If you add 1 to both sides you get A=-3 To check the answer plug A back in. 2-(3-(-3))=-4 The negatives cancel each other out, making the equation 2-(6)=-4 or 2-6=-4 which is correct.

User Mr Anderson
by
5.7k points